2014 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2014
DOI: 10.1109/icassp.2014.6853755
|View full text |Cite
|
Sign up to set email alerts
|

Compressed sensing with unknown sensor permutation

Abstract: International audienceCompressed sensing is the ability to retrieve a sparse vector from a set of linear measurements. The task gets more difficult when the sensing process is not perfectly known. We address such a problem in the case where the sensors have been permuted, i.e., the order of the measurements is unknown. We propose a branch-and-bound algorithm that converges to the solution. The experimental study shows that our approach always retrieves the unknown permutation, while a simple convex relaxation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 11 publications
0
47
0
Order By: Relevance
“…By expanding the determinant with respect to the first and the third row of D, it can be checked that det(D) is again quadratic in terms of λ, where the coefficient of λ 2 is given by the determinant ofD whereD given by Eq. (13).…”
Section: ) Total Number Of Cycles Is Greater Than or Equal To Kmentioning
confidence: 95%
See 2 more Smart Citations
“…By expanding the determinant with respect to the first and the third row of D, it can be checked that det(D) is again quadratic in terms of λ, where the coefficient of λ 2 is given by the determinant ofD whereD given by Eq. (13).…”
Section: ) Total Number Of Cycles Is Greater Than or Equal To Kmentioning
confidence: 95%
“…They propose a branch-and-bound algorithm for solving the problem. The main difference in the framework of that work from ours is the fact that in [13] multiple observations are available under the same permutation matrix Π which, together with the sparsity assumption, simplifies the task of estimating the unknown permutation.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A variant, where the measurement matrix suffers from errors is also studied, and the corresponding maximum likelihood (ML) estimator can be found efficiently via numerical algorithms [3][4][5][6]. Recently, a parameter estimation problem where the observations are perturbed by an unknown permutation matrix has been studied extensively [7][8][9][10][11]. In [7], a branch and bound algorithm utilizing sparsity information is proposed and numerical results show that the unknown permutation can be correctly retrieved.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, a parameter estimation problem where the observations are perturbed by an unknown permutation matrix has been studied extensively [7][8][9][10][11]. In [7], a branch and bound algorithm utilizing sparsity information is proposed and numerical results show that the unknown permutation can be correctly retrieved. In the absence of noise, it is shown that as long as the number of measurements is twice as many as that of unknown parameters under random linear sensing strategy, exact recovery is possible [8].…”
Section: Introductionmentioning
confidence: 99%